Overview of preparation methods of polymeric and lipid-based (niosome, solid lipid, liposome) nanoparticles: A comprehensive review. Issue 6 (13th April 2018) - Amoabediny, Ghasem; Haghiralsadat, Fateme; Naderinezhad, Samira; Helder, Marco N.; Akhoundi Kharanaghi, Elham; Mohammadnejad Arough, Javad; Zandieh-Doulabi, Behrouz
ABSTRACT: A wide number of drug nanocarriers have emerged to improve medical therapies, and in particular to achieve controlled delivery of drugs, genes or gene expression-modifying compounds, or vaccine antigens to a specific target site. Of the nanocarriers, lipid-based and polymeric nanoparticles are the most widely used. Lipid-based systems like niosomes and liposomes are non-toxic self-assembly vesicles with an unilamellar or multilamellar structure, which can encapsulate hydrophobic/hydrophilic therapeutic agents. Polymeric nanoparticles, usually applied as micelles, are colloidal carriers composed of biodegradable polymers. Characteristics such as loading capacity, drug release rate, physical and chemical stability, and vesicle size are highly dependent on experimental conditions, and material and method choices at the time of preparation. To be able to develop effective methods for large scale production and to meet the regulatory requirements for eventual clinical implementation of nanocarriers, one needs to have in-depth knowledge of the principles of nanoparticle preparation. This review paper presents an overview of different preparation methods of polymeric and novel lipid-based (niosome and solid lipid) nanoparticles. GRAPHICAL ABSTRACT: